2007
DOI: 10.1152/jn.01226.2006
|View full text |Cite
|
Sign up to set email alerts
|

Proactive and Reactive Mechanisms Play a Role in Stepping on Inverting Surfaces During Gait

Abstract: Ankle inversions have been studied extensively during standing conditions. However, inversion traumas occur during more dynamic conditions, like walking. Therefore in this study sudden ankle inversions were elicited in 12 healthy subjects who stepped on a trap door while walking on a treadmill. First, 10 control trials (0 degrees of rotation) were presented. Then, 20 stimulus (25 degrees of rotation) and control trials were presented randomly. EMG recordings were made of six lower leg muscles. All muscles show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 47 publications
5
44
1
Order By: Relevance
“…27 Our results demonstrated a significant increase in muscle activity of fibularis longus after the perturbation. As hypothesized, the group of athletes with less stability demonstrated greater muscle activation than those scoring higher on the SEBT, although this was only apparent immediately after the perturbation.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…27 Our results demonstrated a significant increase in muscle activity of fibularis longus after the perturbation. As hypothesized, the group of athletes with less stability demonstrated greater muscle activation than those scoring higher on the SEBT, although this was only apparent immediately after the perturbation.…”
Section: Discussionsupporting
confidence: 57%
“…6,30 It has also been proposed that greater preactivation of the fibularis muscles prior to inversion stress may overcome the electromechanical delay (from activation to force production of the muscle), which could result in a larger spindle response. 11,27 Nonelastic adhesive tape has been used for injury prevention and during rehabilitation after ankle injury. This type of tape has been shown to be effective in restraining ankle inversion, and its use may decrease the incidence of ankle sprains.…”
Section: T T Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…refl ex activity of the stabilising ankle musculature could protect ankle joint from ligament injury. Further, it was recently suggested that refl ex activity of the stabilising ankle muscles could substantially reduce ankle joint loading in case of ankle sprain motion [15,30] . However, so far no data exist concerning the preventive eff ects of several weeks WBV training on refl ex activity of the stabilising ankle musculature during induced perturbed ankle inversion.…”
Section: Neuromuscular Ankle Joint Stabilisation After 4-weeks Wbv Trmentioning
confidence: 99%
“…The human locomotor system can react quickly to unpredictable conditions, but it can also produce predictive adjustments in response to persistent perturbations (Marigold and Patla 2005;Nieuwenhuijzen and Duysens 2007;Sorensen et al 2002). Adaptive mechanisms are therefore critical for optimising coordination patterns and allow individuals to maintain stability and eYciency of walking and balancing behaviours De Nunzio et al 2005;Diekmann et al 2004;Richards et al 2007).…”
Section: Introductionmentioning
confidence: 99%